Early prevention of obesity - Claudio Maffeis (Hygeia Press di Corridori Marinella, 2014)
Childhood obesity is the metabolic disorder with the highest prevalence in both children and adults. Urgency to treat and prevent childhood obesity is based on the clear evidence that obesity tends to track from childhood to adulthood, is associated to morbidity also in childhood and to long-term mortality. Early life, i.e., intrauterine life and the first two years, is a sensitive window for prevention. Anatomical and functional maturation of the hypothalamic structures devoted to regulating energy intake and expenditure and body size mainly occurs in the first 1,000 days of life. Therefore, factors affecting the foetal exposition to maternal metabolic environment and early postnatal nutrition are crucial in modulating the definition of the metabolic programming processes in the brain. Maternal diseases, mainly malnutrition for defect or excess, obesity and diabetes, placental disorders and dysfunctions, maternal use of alcohol and drugs, smoking, affect long term metabolic programming of the foetus with lifelong consequences. Similarly, early nutrition contributes to complete the long-term metabolic regulating framework initiated in the uterus. Breastfeeding, adequate weaning, attention to portion size and diet composition are potential tools for reducing the obesity risk later in childhood. Longitudinal randomized controlled studies are needed for exploring the efficacy of obesity prevention strategies initiated after conception. Proceedings of the 10th International Workshop on Neonatology · Cagliari (Italy) · October 22nd-25th, 2014 · The last ten years, the next ten years in Neonatology Guest Editors: Vassilios Fanos, Michele Mussap, Gavino Faa, Apostolos Papageorgiou